Cyberspace and Instability - Shires, James; Chesney, Robert; Smeets, Max (Edinburgh University Press, 2023)
A wide range of actors have publicly identified cyber stability as a key policy goal but the meaning of stability in the context of cyber policy remains vague and contested. Vague because most policymakers and experts do not define cyber stability when they use the concept. Contested because they propose measures that rely - often implicitly - on divergent understandings of cyber stability. This volume is a thorough investigation of instability within cyberspace and of cyberspace itself. Its purpose is to reconceptualise stability and instability for cyberspace, highlight their various dimensions and thereby identify relevant policy measures. This book critically examines both 'classic' notions associated with stability - for example, whether cyber operations can lead to unwanted escalation - as well as topics that have so far not been addressed in the existing cyber literature, such as the application of a decolonial lens to investigate Euro-American conceptualisations of stability in cyberspace.